Thermoelectric behavior of carbon fiber reinforced lightweight concrete with mineral admixtures - Demirel, Bahar; Yazicioglu, Salih (Elsevier, 2008)
Carbon fiber reinforced concrete can be used to sense temperature owing to the Seebeck effect caused by the p-type conductivity of short carbon fibers. Both the temperature sensing ability of the carbon fiber reinforced lightweight concrete and the influence of mineral admixtures on the Seebeck effect were investigated by measuring the thermo electric power of six Portland cement-based concretes with or without carbon fibers or mineral admixtures ( fly ash, silica fume). It was found that the carbon fiber reinforced lightweight concretes had a Seebeck effect similar to the carbon fiber reinforced normal concrete, but their Seebeck coefficients were decreased by mineral admixtures. Carbon fiber reinforced lightweight concrete with mineral admixtures can be used as a thermal sensor in buildings.
Keywords: carbon fibers; lightweight concrete; seebeck effect; silica fume; fly ash